Radicalism in Ali Jinnah's Land, Religion or Group Matters? - Alauddin, Muhammad Badat; Zuhair, Rofi Hamzah; Al-Haidary, Abdullah Haq (Al-Karim: International Journal of Quranic and Islamic Studies, 2023)
This article examines the issue of radicalism in Pakistan, often identified as the "Land of Ali Jinnah," reflecting the values and vision of its founder, Muhammad Ali Jinnah. Radicalism has been a deep-seated issue in Pakistan, with debates over whether religious or group factors play a more critical role in strengthening radical movements in the country. This article examines the historical development of radicalism in Pakistan, analyzes the factors that influence the spread of radical ideology, and considers the implications of this view on regional and global stability. Through a comprehensive analytical approach, it explores the role of religion as a central element in radicalism in Pakistan, highlighting the role of incorrect or extreme religious understandings in motivating individuals to engage in radical activity. It also examines how group factors such as economic inequality, political discontent and ethnic tensions are essential in strengthening radical movements in Pakistan. The result is that some extremist thinking is based on some of the conservative madrassa education curricula, and some people who lack access to education are, therefore, easily duped and pitted by vested interests. The importance of understanding the balance between religion and group factors in the context of radicalism in Pakistan is that prevention and countermeasures can be more effective. This investigation provides greater insight into the complexity of the issue. It provides a basis for formulating better strategies to address radicalism in the country, which will positively impact regional and global peace and stability. Contribution: This study contributes to a deeper understanding of radicalism in Pakistan by highlighting the interplay between extreme religious interpretations and socio-political conditions, providing a foundation for more effective counter-radicalism strategies.